ANALISIS KESESUAIAN FUNGSI POHON DAN MODEL ARSITEKTURNYA DI RUMAH SAKIT IDAMAN BANJARBARU - Rilo Nurohman Prasetio; Setia Budi Peran; Sulaiman Bakri (Jurnal Sylva Scienteae, 2021)
Green open spaces are spaces in the city in the form of areas, extending in the form of lines, or are open without buildings. Planting plants by taking into account aspects of the suitability of the function and model tree architecture can maximize the existing landscape. This research was conducted to find out the types of trees that grow and find out their suitabilitybased on the tree architecture model in the area.The study was conducted at the Banjarbaru Idaman Hospital. The method used in this research is inventory, interview, evaluation, design and description. The research area is divided into 4 areas. The results of the tree inventory found 25 species of trees belonging to 16 families, and 8 architectural models. The tree architectural models found are Attim, Aubreville, Corner, Petit, Rauh, Roux, Scarrone and Troll. Based on the results of the overall evaluation of the trees that grow in the area of the Banjarbaru Idaman Hospital is considered quite appropriate.Keywords: Suitability of functions and types, tree architecture, Banjarbaru Idaman Hospital